2021
DOI: 10.1021/jacs.1c07690
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Complexity of Supramolecular Copolymerization Dictated by Triazine–Benzene Interactions

Abstract: Supramolecular copolymers formed by the noncovalent synthesis of multiple components expand the complexity of functional molecular systems. However, varying the composition and microstructure of copolymers through tuning the interactions between building blocks remains a challenge. Here, we report a remarkable discovery of the temperature-dependent supramolecular copolymerization of the two chiral monomers 4,4′,4″-(1,3,5triazine-2,4,6-triyl)tribenzamide (S-T) and 4,4′,4″-(benzene-1,3,5-triyl)tribenzamide (S-B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Below 70 °C, the fractions of the 1−1 homointeraction and the 1−2/2−1 heterointeractions increased, which nicely reflected the incorporation of a considerable amount of 1 (Figure 4H, center). 47 Importantly, the fractions of all interactions became almost equal at 20 °C, which corroborated the copolymerization of 1 and 2, i.e., SP spiral , had a random sequence of the two monomers (Figure 4H, right).…”
Section: ■ Results and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Below 70 °C, the fractions of the 1−1 homointeraction and the 1−2/2−1 heterointeractions increased, which nicely reflected the incorporation of a considerable amount of 1 (Figure 4H, center). 47 Importantly, the fractions of all interactions became almost equal at 20 °C, which corroborated the copolymerization of 1 and 2, i.e., SP spiral , had a random sequence of the two monomers (Figure 4H, right).…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…Importantly, an inflection point suggesting the onset of spontaneous nucleation of 1 was not recognized around T e ′[ 1 ], which would have been clearly visible if their narcissistic self-sorting had occurred, as indicated by the simple summation (black circles) of the individual polymerization curves of 1 (red circles) and 2 (yellow circles). This observation suggested that 2 initially nucleated upon cooling the mixture and 1 was gradually incorporated in the elongation process of 2 . , Indeed, the variation in the monomer composition ( 1 : 2 = 2:1 and 1:2) while keeping c t at 400 μM resulted in similar nonsigmoidal curves with T e ′, which was almost identical to T e ′[ 2 ] at the same concentrations (Figure S12). The subsequent heating of the cooled 1:1 mixture at a rate of 1 °C min –1 provided a depolymerization curve that matched well with the polymerization curve.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…For convenient access to enantiopure Pt­(II) complexes, we utilized chiral induction from a commercially available chiral source. This strategy has been commonly utilized in supramolecular, polymer, and coordination chemistry, including platinum complexes. , Recently, planar chirality and helicity inductions of Pt­(II) complexes for CPP emitters have been using axial and point chirality . In this study, we demonstrated the helical induction of d-π-conjugated iminopyrrolyl Pt­(II) complex 1 by the point chirality of 1,2-diaminocyclohexane (Figure ).…”
Section: Introductionmentioning
confidence: 70%
“…However, assembly behaviours in reality can be extremely complicated, and multiple metastable or kinetically-trapped states can be involved during the process. [133][134][135] Therefore, by elongating the transformation time between a meta-stable and thermodynamically stable state, in other words, making the self-sorting assemblies kinetically trapped is also a very effective approach to achieve selfsorting assembly. A fascinating kinetically-trapped self-sorting system, which consisted of the enantiomers of the perylene bisimides derivative (PBI1) and controlled by differentiating the cooling speed, was reported by Wu ¨rthner et al 136 When cooling down from 90 1C to 20 1C, PBI1 assembled into homochiral fibres at a cooling rate of 10 K min À1 , but formed a heterochiral sheet at 0.6 K min À1 .…”
Section: Temporal Controlmentioning
confidence: 99%